ANALISIS POTENSI SEKTOR UNGGULAN DALAM PEREKONOMIAN KABUPATEN SIDENRENG RAPPANG - Hatta, Muhammad (Economos : Jurnal Ekonomi dan Bisnis, 2019)
This study aims to determine the leading sectors in the regional economy Sidenreng Rappang Regency. The data collection techniques used in this study is 17 sectors economy in GRDP Sidenreng Rappang Regency. Technical data analysis in this study using Klassen?s Typology Analysis, Location Qoutient (LQ) Analysis and Analysis Shift Share. Based on the Klassen Typology analysis which entered as a sector classification advanced and growing rapidly (si > s and ski > sk) is the Agriculture Sektor, Forestry, and Fisheries; Processing Industry Sektor; and the Construction Sector. Based on Analysis Location Qoutient (LQ) which is the base sector (LQ > 1) is the Agriculture Sector, Forestry, and Fisheries; Processing Industry Sector: Electricity and Procurement Sector Gas; Construction Sector; Real Estate Sector; and the Goverment Adminitstration Sector, Defense and Mandatory Social Security. Based on the Shift Share Analysis of the economic sector with a positive shift of differential or competitive interest (Cij) is the Sector Agriculture, Forestry, and Fisheries; Mining and Excavation Sector; Sector Processing Industry; Construction Sector; Transportation and Warehousing Sector; Sector Information and Communication; and the Financial and Insurance Services Sector. Based on three the analysis becomes the leading sector in the regional economy of the Sidenreng Rappang Regency is the Agricultur, Forestry and Fisheries Sector; Sector Industrial Processing; and Construction Sector.